MENGATASI STRESS DI MASA PANDEMI COVID 19 - novita anggraini (IKesT Muhammadiyah Palembang, 2022)
Covid-19 is a disease caused by the corona virus and was discovered in 2019 and then reported to the WHO. Covid-19 has spread to various countries in the world, including Indonesia. The outbreak of this epidemic has also increased the number of positive cases of Covid-19. As a result, the whole world, including Indonesia, is experiencing the impact of the health and economic crisis. People's lives seem to have stopped because of restrictions, including schools, work, health services, and so on. This can cause panic, fear and anxiety in the community. So, it is necessary to carry out activities for the community to manage stress during this pandemic. Purpose: to overcome stress during the COVID-19 pandemic, prevent the occurrence of risky behavior on health in RT 006 RW 002 residents who want to implement healthy and clean living behaviors. Method: provide counseling and discuss with residents of RT 006 RW 002 Sukajaya Palembang. In community service which was carried out on 30 people, before conducting counseling the community service team conducted oral interviews with participants. All participants (100%) who took part in the activity felt stressed because of the covid 19 pandemic, especially with the news related to covid 19 which was increasing every day being affected by covid 19, they were afraid of being affected too. The Community Service Team conducted counseling related to